Effects of whole body vibration training combined with blood flow restriction on muscle adaptation. Issue 2 (1st February 2021) - Cai, Zong-Yan; Wang, Wen-Yi; Lin, Jia-De; Wu, Chih-Min
Abstract : This study investigated the effects of whole body vibration (WBV) training combined with blood flow restriction (BFR) on muscle fitness. Twenty physically inactive adults were randomly assigned to a WBV + BFR group (8 men and 2 women) and a WBV group (8 men and 2 women). The participants in the WBV group were subjected to 10 sets of intermittent WBV exercise 20 min/day, 3 days/week, for 8 weeks. The participants in the WBV + BFR group received the same WBV treatment, but the proximal portion of their thighs was compressed using inflatable cuffs. Dual-energy X-ray absorptiometry estimated thigh muscle mass, one repetition maximal (1RM) leg press, and muscle endurance were measured before and after the training programme. The results indicated that thigh muscle mass significantly increased (3%) after the 8-week training period only in the WBV + BFR group. Meanwhile, 1RM leg press and muscle endurance significantly increased in both groups after training ( p < 0.05). Analysis of covariance revealed that the increase in 1RM leg press and muscle endurance was significantly higher ( p < 0.05) in the WBV + BFR group than the WBV group (leg press: 11.1%. vs. 4.37%; muscle endurance: 48.84% vs. 15.19%, respectively). In conclusion, exposure to regular WBV + BFR training can increase thigh muscle mass, maximal strength, and muscle endurance compared with exposure to WBV training alone. WBV + BFR training appears to be a feasible strategy for improving muscle mass, strength, and endurance in previously untrained participants.